EFL Pre-service Teachers’ Leadership Project Practices in Indonesia's Teacher Professional Development Program - Janu, Gregoriana Nobilio Pasia; Kuswandono, Paulus (VELES Voices of English Language Education Society, 2023)
Indonesia's Ministry of Education has integrated the Leadership Project course into the Pendidikan Profesi Guru (PPG) program, emphasizing the development of professional qualifications and leadership skills among EFL pre-service teachers. This study scrutinizes the influence of both conceptual and practical frameworks of the course on cultivating leadership competencies. It poses two pivotal questions: Firstly, how do pre-service EFL teachers perceive these frameworks within leadership projects? Secondly, what challenges do they face in executing these projects effectively? Utilizing an explanatory mixed-methods design, the study collated and analyzed data from 31 participants through surveys and inductive thematic coding. It revealed that while EFL pre-service teachers have a positive reception of leadership involving collective knowledge and change initiation, they also report significant hurdles. Implementing complex frameworks like Sustainability NEWS (Nature, Economy, Well-being, Society) and Appreciative Inquiry presented difficulties, predominantly due to time limitations and communication barriers with target groups. Furthermore, a gap in understanding the conceptual underpinnings led to complications in the planning and sustainable implementation of projects, exacerbated by tight schedules and financial restrictions. Feedback from participants highlighted a need for program enhancements, suggesting refined policies, more rigorous consultation processes, and an enriched focus on reflective practices. The study offers valuable insights into the perceptions of EFL pre-service teachers regarding leadership programs.